Cassava Production Efficiency in Southern Ethiopia: The Parametric Model Analysis - Tafesse, Alula; Mena, Bekele; Belay, Abrham; Aynekulu, Ermias; Recha, John W.M.; Osano, Philip M.; Darr, Dietrich; Demissie, Teferi Dejene; Endalamaw, Tefera B.; Solomon, Dawit (Frontiers Media, 2021)
Due to capital constraints and land scarcity in developing countries, introducing new technology to boost productivity is difficult. As a result, working to improve cassava production efficiency is the best option available. Cassava is increasingly being used as a food source as well as an industrial raw material in the production of economic goods. This study estimates cassava production efficiency and investigates the causes of inefficiency in southern Ethiopia. Cross-sectional data from 158 households were collected using a systematic questionnaire. The Cobb-Douglas (CDs) stochastic frontier production model was used to calculate production efficiency levels. The computed mean result showed technical efficiency (TE), allocative efficiency (AE), and economic efficiency (EE) levels of 74, 90, and 66%, respectively. This demonstrated that existing farm resources could increase average production efficiency by 26, 10, and 34%, respectively. The study found that land size, urea fertilizer application, and cassava planting cut all had a positive and significant effect on cassava production. It was discovered that TE was more important than AE as a source of benefit for EE. Inefficiency effects modeled using the two-limit Tobit model revealed that household head age, level of education, cassava variety, extension contact, rural credit, off-farm activities involvement to generate income, and farm size were the most important factors for improving TE, AE, and EE efficiencies. As a result, policymakers in government should consider these factors when addressing inefficiencies in cassava production. It is especially important to provide appropriate agricultural knowledge through short-term training, to provide farmers with access to formal education, to access improved cassava varieties, and to support agricultural extension services.